Impact of nutritional education on the nutrient intake of type 2 diabetes mellitus patients - Skórska, Katarzyna; Zabłocka-Słowińska, Katarzyna; Dobrzyńska, Natalia; Grajeta, Halina (Progress in Nutrition, 2019)
Introduction: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder affecting the metabolism of carbohydrates and characterized by hyperglycemia, inadequate secretion of insulin, and/or peripheral insulin resistance. The most common method of T2DM treatment is still pharmacotherapy, due to its convenience. However, diet is one of the most important factors in the development and progression of this disease, and can make an important contribution to the treatment of T2DM. Purpose: The aim of the research was to evaluate the effects of nutritional education on the nutrient intake of T2DM patients. Material and methods: A total of 149 patients were enrolled (99 women and 59 men) aged 36-88, all diagnosed with T2DM or glucose metabolism disturbances. Nutrient intakes per subject were evaluated based on 24h dietary recall from the previous three days. Anthropometric measurements were also performed. Results: Intakes of various nutrients in the diet of T2DM, both under the care of a dietician and not, did not usually meet dietary recommendations. The diets of T2DM patients under the care of a dietician, despite significant dietary mistakes, provided significantly more nutrients with potential positive effects on carbohydrate and lipid metabolism: fiber, EPA, DHA and PUFA, minerals: K, Mg, Fe, Cu and Mn as well as vitamins and smaller amounts of the nutrients which are nutritional risk factors for the development and progression of T2DM: total amount of fat, SFA, Na and P. Conclusion: Nutritional education has a positive impact on the nutrient intake of T2DM patients. Routine dietitian care for people suffering from this disease should be recommended.